Performance of Regulated Agricultural Markets: Perception of Farmers in Salem District, Tamil Nadu - Shakeel-Ul-Rehman, (Indian Journal of Marketing, 2015)
Although India has achieved self-sufficiency in food grain production (more than 230 million tonnes in 2011-12), but it is still characterized by low levels of productivity due to degradation of natural resources and lack of technological&infrastructural facilities. Unfortunately, unfavorable price regime and low level of value addition activities have also contributed to the out-migration of the farmer class from the rural areas. To secure the agrarian community of the country, India has brought regulations in the agricultural sector, especially in output marketing of agricultural produce. The government has put in serious efforts in bringing all the agricultural markets of the country under the Agricultural Produce Marketing Committee Act, which restricts the sale of agricultural produce anywhere except in the regulated agricultural markets (RAMs). These regulated agricultural markets are direct sale markets monitored by the District Agricultural Marketing Committees of the respective state governments. The present research attempted to bring into light whether these markets were functioning according to the expectations of the sellers/farmers. The study used binary logistic regression, correlation analysis, and other statistical tools to discover the underlying dimensions of various indicators with regard to the overall satisfaction of the sellers/farmers with the performance of the RAMs located in Salem District of Tamil Nadu. Most of the variables/indicators related to market performance were rated on the positive side of the scale by the respondents, thereby concluding that the farmers had a positive perception of the concerned RAMs.